Enhanced early hydration properties of Nano Silica incorporated cement paste - Sreh, Muftah Mohamed (Sharwes Scientific Journal, 2022)
In the direction of evaluate the influence of nano silica particles (NS) on calcium silicate hydrate (CSH) formed at early-stage, hydration of tricalcium silicate (C3S), hydration rate and Ca (OH)2 content of hydration products were measured. An experimental study was carried out on five mixes of cement paste with water/cement ratio of 0.28 by weight. The studied dosages of NS are 0.5%, 1%, 1.5% and 2% by weight of cement as an addition. The degree of hydration was measured by Thermo-Gravimetric Analysis test (TGA) after 1 day. TGA allows determination of the amount of water bound in portlandite, and the total amount of chemically bound water. TGA was used to calculate all Differential Thermal Analysis (DTG) curves, TG curves, mass losses and temperature peaks by using apparatus software. It was concluded that adding of NS to cement paste up to 2%, NS improves the microstructural characteristics in comparison with the neat cement paste. The test results shows that NS be good not only as filler to improve the microstructure, but also as an activator to enhance the pozzolanic reaction, which promote the formation of hydrated products. Furthermore, the CSH gel of cement paste increases with the increase of NS content, which finally leads to the more compact and dense structure of hardened paste.